LINKING AN INTEGRATED APPROACH OF EMPOWERMENT TO EMPLOYEE CREATIVITY - Amro Al-Madadha; Dimitrios N. Koufopoulos (European Scientific Journal, ESJ, 2014)
Nowadays, considerable attention has been paid to employee creativity in organizations. Therefore, much studies have proposed various approaches to motivate employee creativity in organization. Accordingly, we will conduct a review of different empowerment approaches and employee creativity literature in organizations. The present paper offers insight on how different theories of leadership and empowerment can influence creativity of employees. The paper will start framing different approaches of empowerment. Specifically, empowering leadership, empowerment climate, psychological empowerment. This synthesize of various theories of empowerment has been depicted in an integrated approach of empowerment model. This model describes the mechanism for empowering leadership, empowerment climate and psychological empowerment and their influence on employee creativity.